PENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF QUICK ON THE DRAW PADA SISWA KELAS II SEKOLAH DASAR - Sumargiyani Sumargiyani (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2014)
The teacher-centered learning causes less active students during the learning process. Application of learning method using cooperative learning model Quick on the Draw at the second grade students of SD Muhammadiyah Kleco III Yogyakarta can improve learning activities of the students. The Classroom Action Research conducted in three cycles, with the research object is 31 students. Data were collected using observation sheet and interview session. Furthermore, data were analyzed using qualitative descriptive analysis. It is obtained that the percentage of student learning activities from Cycle I is 70.51% (good), Cycle II is 78.56% (good) and Cycle III is 87.095% (very good). Based on the interviews, it is obtained that most of students are interested and feel happy in the learning of mathematics using cooperative learning model Quick on the Draw.